Developing . NET web services with XML - Jorgensen, David (Rockland, MA : Syngress Pub., 2002)
Prepare for the next generation of the internet with this in-depth, developer's guide to the .Net framework that utilizes XML to achieve greater flexibility of information and increased interoperability. Developing .Net Web Services with XML introduces readers to the foundation for the .Net platform. The book covers the history, applications and implementation of the Extensible Markup Language within Microsoft's .NET framework. Readers will be given a thorough introduction to .NET and its XML building blocks while acquiring a firm grasp of how those blocks can be used to build any Web site or service so that it will federate and collaborate seamlessly with others Equips developers with the tool necessary to take advantage of the next generation of the internet This book will provide web developers with a firm understanding of XML, the building block of the .Net framework Includes practical, real-life applications using XML Unrivalled web based support: Readers can receive up-to-the minute links, white papers and analysis for two years at solutions@syngress.com.
What are web services? -- Introduction to the Microsoft .NET framework -- XML fundamentals -- Information exchange using the simple object access protocol (SOAP) -- WSDL and UDDI -- Building an ASP.NET/ADO.NET shopping cart with web services -- Building a SQLXML web service application -- Building a jokes web service.
Includes index.
Keywords: XML (Document markup language); Electronic books